Stomatocystis goerresi, a new species of gregarine parasite (Apicomplexa, Monocystidae) from the invasive Japanese earthworm Amynthas tokioensis (Megascolecidae), with a description of the parasite's life cycle - Schall, Joseph J (Folia parasitologica, 2021)
Stomatocystis goerresi sp. n., a gregarine (phylum Apicomplexa, Monocystidae) parasite of an important invasive earthworm in North America, Amynthas tokioensis (Beddard), is described. This is the second species placed into the genus, and details of its morphology and life cycle support Stomatocystis Bandyopadhyay, Mitra et Göçmen, 2006 as a valid taxon. The new species is described using standard nomenclature, measurements, shape descriptors, and photographs of living cells. The parasite was found only in A. tokioensis, and absent in sympatric earthworm species, suggesting it arrived when the earthworms were introduced from their origin from Japan. The species is distinctive from the type species in the genus, S. indica Bandyopadhyay, Mitra et Göçmen, 2006, in being substantially larger in all stages, found in only the host's seminal vesicles, and found in a different host species from East Asia. The distinctive trophozoites/gamonts develop a large funnel structure ringed with a collar of pronounced ridges, and the funnel appears even in the smallest cells. This funnel varies greatly in relative size (to the cell body) and shape, sometimes forming a large fan. The life cycle of S. goerresi is described including distinctive syzygy in which the funnels fuse and then produce a large cell with local centres of isogamete production (thus sex without gender). Gametes are large ( ~5 μm) spheres with complex tips. Oocyst production is large, > 1,000 per mature gametocyst. The genus Stomatocystis is placed into the Monocystidae, but the life cycle of the new species differs from those of other monocystid taxa, which may mean the Monocystidae are not monophyletic or life cycles are variable within the family. Prevalence of S. goerresi at the type locality was high (~ 90%). The parasites destroy the earthworm's organ of sperm self-storage thus eliminating the male function in the hermaphroditic host which may influence the ability of the earthworm to invade and be successful at new sites.
Keywords: host specificity; introduced species; Japonsko; Apicomplexa; Life Cycle Stages; mužské pohlaví; Oligochaeta; protist; zvířata; zavlečené druhy; Male; Introduced Species; standardised diagnostic morphology; stadia vývoje; Japan; Animals